Synthesis, stability and conductivity of SrCe0.8-xZrxY0.2O3-δ as electrolyte for proton conducting SOFC. (20th November 2016) - Mahadik, Pooja Sawant; Jain, Dheeraj; Shirsat, A.N.; Manoj, N.; Varma, S.; Wani, B.N.; Bharadwaj, S.R.
Abstract: Strontium cerate (SrCeO3 ) exhibits proton conductivity in humidified atmosphere at elevated temperature. However this material is unstable in CO2 and H2 O atmosphere. Thought its proton conductivity is lower than barium cerate (BaCeO3 ) there is scope to improve its stability, sinterability and ionic conductivity by substituting suitable cations at B-site. SrCe0.8-x Zrx Y0.2 O3-δ (SCZY, with x = 0.0, 0.2, 0.4, 0.6 and 0.8) powders were synthesized by sol gel route. Lattice parameters were generated from powder XRD data and it was found that with increase in Zr content the cell volume reduces. Chemical stability of sintered SCZY samples was evaluated in 100% CO2 using TG-DTA up to 1173 K and also in boiling water. Zirconium doped samples exhibit enhanced chemical stability in presence of carbon dioxide and boiling water, with x ≥ 0.4 compositions having no effect of both the reactive gases. Proton conductivity of SCZY samples were measured in moist N2 atmosphere. Activation energy for proton conduction was also evaluated.